Study of Knowledge, Attitude and Action of Buffalo Breeders in the Villages Around Nagan Raya Power Plant on the Impact of Fly Ash Exposure - Ira Susanti; Rinidar Rinidar; Sugito Sugito (The Faculty of Veterinary Medicine of Syiah Kuala University, 2018)
One of the biggest contributors of air pollution is the production of coal fly ash from power plant industry. Fly ash has an immediate impact on human and animal health around the power plant. Many buffaloes in Nagan Raya usually grazing near the 110-megawatt steam power plant that using low rank coal. This action raises concerns about buffalo’s health due to exposure to fly ash. This study aimed to examine the relationship of knowledge, attitude and action of buffalo breeders to the impact of fly ash exposure on the buffaloes. This research used analytical survey with cross sectional design. This study was conducted in February 2018 with 30 respondents from four villages around Nagan Raya Power Plant to evaluate their knowledge, attitudes and actions by using questionnaires. The data were analyzed statistically with Chi Square Test with SPSS for Windows version 17.0. The results showed that there was no significant correlation between the knowledge of buffalo breeders and the impact of fly ash exposure (P 0.05), while the attitude and actions of buffalo breeders had a significant correlation with the impact of fly ash exposure (P 0.05). These results concluded that the buffalo breeders in the villages around the power plant did not realize the impact of fly ash arising from coal of power plant. It is expected that the associated institution would conduct a counseling about the impact of fly ash exposure as well as good management of buffaloes.